The existence of foreign language anxiety in an intermediate english level at Centro de Enseñanza de Idiomas de la Universidad De El Salvador (CENIUES) - González Salinas, Cindy Yasmin
The present study pursued to find out if Foreign Language Anxiety is an issue that occurs in CENIUES. Before carrying out this research, a variety of information about Foreign Language Anxiety was collected in order to know important aspects of it on this process. Roughly, it can be said that different learning situations cause a certain degree of anxiety on students. However, what is more valuable and motive this research was to find out the existence or lack of it in CENIUES. Moreover, this research is inspired by previous studies (Tanveer, 2007; Osboe, Fijimuna et all.) on anxiety issues other countries and those researches indicate that anxiety has some positive and negative effects on students’ oral performance. In addition, even though many research studies have been carried out on anxiety, there is not a specific one that proves if anxiety really exists in CENIUES.